Los naufragados tatuajes by Jorge Velasco Mackenzie: Apostilles to increase documentary confusion - Nieto Cadena, Fernando (2015)
This article dates from March 2009, the Ecuadorian poet Nieto Cadena makes a peculiar exploration and critical reflection of the novel of his contemporary, Jorge Velasco Mackenzie, Tatuaje de náufragos, published in 2008. The text, more than highlighting the achievements of the Velasco’s novel, becomes a firsthand testimony of who was part of the legendary Sicoseo group, a cultural reference in the Guayaquil of the 70s. In addition to demystifying some statements (and misrepresentations) that have been made around the authors who were part of this generation, Nieto Cadena also comments on what the Café Montreal meant in the daily lives of these authors and what relationship it had with the Sicoseo group, of which he was one of the visible heads even before his pilgrimage to Mexico, where he undertook intense literary activity.